Simulation Methods in the Development of Students’ Professional Competence at Higher Medical Educational Institutions - Sabadosh, Rostyslav (Galician Medical Journal, 2018)
The development of practical skills and abilities is one of the most important tasks of students and teachers of higher medical educational institutions. The ensuring of providing an effective and adequate assistance to the patient in an urgent situation is of particular importance. Various simulation methods exist in educational and medical training centers of higher medical educational institutions to practice the methods of providing medical care in emergency situations. The scientific and practical centers are equipped with training phantoms (for suturing deep wound, reducing dislocations) and allow polishing professional skills during practical classes or after them. Simulation methods give an opportunity to objectively assess the correctness of the actions performed by the student, to teach the technique of cardiac massage and artificial respiration, to correct the position of the mannequin head thereby protecting the person who performs resuscitation procedure from infectious agents. The possibility of simulation training and multiple repetitive resuscitation actions practices the students’ ability to work during an emergency until it becomes automatic. The use of simulation training of medical students allowed bringing the level of national science closer to the world standards.